2013
DOI: 10.1155/2013/836738
|View full text |Cite
|
Sign up to set email alerts
|

Indian Craniometric Variability and Affinities

Abstract: Recently published craniometric and genetic studies indicate a predominantly indigenous ancestry of Indian populations. We address this issue with a fuller coverage of Indian craniometrics than any done before. We analyse metrical variability within Indian series, Indians' sexual dimorphism, differences between northern and southern Indians, index-based differences of Indian males from other series, and Indians' multivariate affinities. The relationship between a variable's magnitude and its variability is log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…These points are demonstrated through stepwise discriminant function analysis of crania of known population affinity from India. The results feed into the second goal of this paper, which is to show that a "South Asian" craniometric identity can be discerned at the level of the individual cranium, as well as the population level (as previously demonstrated by Raghavan et al 2013). Raghavan et al (2013) analyzed ten series from northern India and South India, based on measurements recorded by the first author.…”
Section: Goals Of This Papermentioning
confidence: 63%
“…These points are demonstrated through stepwise discriminant function analysis of crania of known population affinity from India. The results feed into the second goal of this paper, which is to show that a "South Asian" craniometric identity can be discerned at the level of the individual cranium, as well as the population level (as previously demonstrated by Raghavan et al 2013). Raghavan et al (2013) analyzed ten series from northern India and South India, based on measurements recorded by the first author.…”
Section: Goals Of This Papermentioning
confidence: 63%
“…A majority of these classifications were within the Indian subcontinent, suggesting the level of heterogeneity in the anatomical sample is not necessarily exclusive evidence for non‐Indian sources of anatomical specimens. The cranial variability noted among the anatomical crania suggests the variability in India is much higher than previously considered, a finding supported by recent work on cranial variation among modern Indian individuals . When anatomical material is encountered in the forensic laboratory, a reference sample is necessary for craniometric comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…When South Asians and southwestern Asians were introduced to the comparisons, Wright (2002) found that Andamanese were closer to them than to sub-Saharan Africans, while Stock et al (2007), adjusting for size, found that Andamanese clearly clustered with South Asians to the exclusion of other populations. On the other hand, Raghavan et al (2013), also adjusting for size, find that Andamanese cluster with sub-Saharan Africans and are clearly distinct from South Asians. In sum, Andamanese crania show a wide range of affinities with Old World crania, apart from Southwest Pacific crania; however, a sub-Saharan African affinity is perhaps the most consistent result overall.…”
Section: Review Of Dental Metrical Studies On Negritosmentioning
confidence: 92%